Cu alloy powder for additive manufacturing having high hardness and high electrical conductivity and additive manufacturing body using the same

JP7668843B2Active Publication Date: 2025-04-25SANYO SPECIAL STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023080984
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-05-16
Publication Date
2025-04-25
Estimated Expiration
2043-05-16

AI Technical Summary

Technical Problem

Conventional Cu alloy powders for additive manufacturing face challenges in achieving high relative density, high hardness, and high electrical conductivity due to the adverse effects of adding Ni, which reduces conductivity and does not significantly enhance hardness through solid solution strengthening.

Method used

A Cu alloy powder composition with a regulated Ni/Si mass ratio (Ni: 1.20~7.30%, Si: 0.25~1.80%, Ni/Si: 3.00~6.00, Ni+Si: 1.50~9.00%) is used, along with controlled amounts of Mg, Zr, Cr, Nb, Mn, Fe, Zn, Sn, C, P, S, and Ag, to balance hardness, formability, and conductivity.

Benefits of technology

The Cu alloy powder achieves high relative density, excellent formability, high hardness, and high electrical conductivity, with intermetallic compounds precipitating during aging to enhance precipitation strengthening, maintaining conductivity and improving the balance with hardness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000011_0000
    Figure 00000011_0000
Patent Text Reader

Abstract

To provide a Cu alloy powder for additive manufacturing which can be shaped at a relatively high density and offers high hardness, high electrical conductivity and high thermal conductivity, and a shaped article using the same.SOLUTION: A Cu alloy powder for additive manufacturing contains, in mass%, Ni: 1.20-7.30%, Si: 0.25-1.80%, Mg: 0.40% or less, a total of one or more elements selected from Zr, Cr, Nb, Mn, Fe, Zn and Sn: 0.00-2.00%, C: 0.000-0.020%, P: 0.000-0.020%, and S: 0.000-0.020%, with the balance being Cu and inevitable impurities. In the above components, the ratio of Ni / Si is 3.00-6.00 and the content of Ni+Si is 1.50-9.00%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a Cu alloy powder for additive manufacturing, which has high hardness, excellent formability, and high electrical conductivity, and a molded body thereof. [Background technology]

[0002] Because Cu alloys have high electrical and thermal conductivity, they are used in various coils, heat sinks, electrical contacts, molds, etc. Recently, in order to accommodate complex shapes, trials and investigations are being conducted into the use of additive manufacturing (also known as 3D printers, three-dimensional modeling methods, additive manufacturing, etc.) for their manufacture.

[0003] Generally, according to the Wiedemann-Franz law (the ratio of a metal's thermal conductivity κ to its electrical conductivity δ is a constant value at a constant temperature T, regardless of the type of metal), the thermal conductivity of a metal is correlated with its electrical conductivity. Therefore, here, matters relating to both physical properties will be explained using only electrical conductivity.

[0004] Now, when Cu powder is used for additive manufacturing, the Cu powder reflects the laser beam, which is often used as a heat source for additive manufacturing. Therefore, even if Cu powder is used for additive manufacturing, it is difficult to sufficiently raise the temperature of the Cu powder to melt it and obtain a molded body with high relative density and no residual pores.

[0005] Therefore, attempts have been made to obtain Cu alloy additive bodies with high relative density by adding various additive elements such as Ni to reduce the laser reflectance of the Cu alloy powder (or increase the laser absorption rate) and make it easier to melt (see Patent Documents 1, 2, and 3).

[0006] However, the addition of excessive Ni reduces the electrical conductivity of the molded body, thereby impairing the excellent physical properties that Cu originally possesses.

[0007] In addition, in recent years, the application of additive manufacturing methods to Cu alloy products used in environments where they are under stress or in contact with other components has begun to be considered. In order to withstand these environments, Cu alloy additive manufacturing products are also required to be hard. However, the effect of Ni on the required hardness of Cu alloy additive manufacturing products has not been studied in detail and has not been given sufficient consideration. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2021-17639 A [Patent Document 2] Patent Publication No. 2022-188809 [Patent Document 3] International Publication No. 2018 / 199110 Summary of the Invention [Problem to be solved by the invention]

[0009] When conventional Cu alloy powders are used for additive manufacturing, it has been difficult to find a Cu alloy shaped body or its raw material powder that has excellent formability (ability to be shaped to a high relative density), high hardness, and high electrical conductivity. Therefore, the present invention aims to provide a Cu alloy powder for additive manufacturing and a shaped body thereof that can combine high levels of hardness, formability, relative density, and electrical conductivity.

[0010] However, if one attempts to increase the amount of Ni added to improve formability in response to laser reflection, it results in a significant decrease in electrical conductivity, making it difficult and not easy to achieve both high levels of formability and electrical conductivity.

[0011] In addition, because Ni is an element that easily dissolves in Cu in forged materials, even if the study focuses on solid solution strengthening as the main effect of Ni on hardness, it is unlikely that a significant increase in hardness can be obtained through solid solution strengthening because there is no significant difference between the atomic radii of Cu and Ni. Therefore, it is difficult to derive a solution from the general idea of ​​solid solution strengthening.

[0012] Therefore, the problem that the present invention aims to solve is to provide a Cu alloy powder for additive manufacturing that has excellent moldability, allowing it to be molded to a high relative density, and has high hardness, high electrical conductivity, and high thermal conductivity, as well as a molded body made using the same. [Means for solving the problem]

[0013] As described above, simply focusing on Ni and increasing the amount of Ni results in a decrease in electrical conductivity, and it is difficult to increase hardness through solid solution strengthening. As a result of extensive research, the present inventors have discovered that in Ni-added Cu, a composition that can balance the hardness, formability, and electrical conductivity of a molded body can be achieved by adding a predetermined amount of Si as a third component in addition to Ni and specifying the Ni / Si mass ratio within a predetermined range, thereby achieving high hardness, excellent formability, and high electrical conductivity.

[0014] There are no documents that have examined in detail the effects of the simultaneous addition of Ni and Si to Cu on the additive manufacturing method and the additive manufacturing body, and this is a new finding that has been revealed for the first time by the present invention. In particular, the additive manufacturing method is a manufacturing method that involves rapid solidification, and it is thought that factors that affect the electrical conductivity and hardness of the additive manufacturing body, such as the crystal grain size, constituent phases, and precipitate formation behavior, are significantly different from those of the melt manufacturing method, and the heat treatment behavior is also different. Furthermore, moldability is a requirement unique to the additive manufacturing method. The present invention was arrived at by comprehensively examining these points.

[0015] That is, the first means for solving the problems of the present invention is In mass%, Ni: 1.20-7.30%, Si: 0.25 to 1.80%, Mg: 0.40% or less, Zr, Cr, Nb, Mn, Fe, Zn, Sn, any one or more of the following in total: 0.00 to 2.00% C: 0.000~0.020%, P: 0.000~0.020%, S: 0.000 to 0.020% The balance is Cu and unavoidable impurities. And in the above components, Ni / Si: 3.00 to 6.00 Ni+Si: 1.50-9.00%; This is a Cu alloy powder for additive manufacturing.

[0016] The second means is a Cu alloy powder for additive manufacturing, which, in addition to the components described in the first means, further contains, by mass%, Ag: 5.00% or less, the remainder being Cu and unavoidable impurities, and in the components, Ni / Si: 3.00-6.00, and Ni+Si: 1.50-9.00%. However, Ag in the second method is excluded from 0%.

[0017] The third aspect of the present invention is a shaped body produced by additive manufacturing using the Cu alloy powder for additive manufacturing according to the first or second aspect of the present invention. Effect of the Invention

[0018] When the Cu alloy powder for additive manufacturing of the present invention is used for additive manufacturing, it is possible to obtain a Cu alloy powder for additive manufacturing that can be molded to a high relative density and has high hardness, high electrical conductivity, and high thermal conductivity, and a molded body using this Cu alloy powder can be obtained.

[0019] By finding that the mass ratio of Ni to Si, Ni / Si, can be set within a specified range, when the molded body is aged, an intermetallic compound having a specified Ni to Si ratio precipitates, making it possible to utilize precipitation strengthening, which is generally considered to have a stronger strengthening effect than solid solution strengthening. Furthermore, by promoting the precipitation (discharge from the Cu matrix) of Ni, which is an easily soluble element, as an intermetallic compound, high electrical conductivity can be obtained.

[0020] Furthermore, by setting the Ni / Si ratio within a predetermined range, it is possible to avoid excessive Ni-richness or Si-richness, so that neither Ni nor Si remains in excessive concentrations in the Cu matrix after precipitation of the above-mentioned intermetallic compounds, and high electrical conductivity is obtained.

[0021] In addition, high electrical conductivity can be obtained by keeping the contents of Mg, Zr, Cr, Nb, Mn, Fe, Zn, and Sn low and by reducing the impurities of C, P, and S.

[0022] The addition of Ag can further improve the balance between hardness and electrical conductivity while maintaining excellent formability. It is believed that Ag in the alloy of the present invention promotes the precipitation of the intermetallic compounds and, when elements such as Zr and Cr are contained, the expulsion of these elements from the Cu matrix. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is a graph with electrical conductivity (% IACS) on the vertical axis and Vickers hardness (Hv) on the horizontal axis, where Examples 1 to 29 are plotted with ◯ and Comparative Examples 1 to 9 are plotted with ×. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Before describing the embodiment of the present invention, the reasons for specifying each component added to the Cu alloy powder of the present invention, and the reasons for specifying the Ni / Si ratio and Ni+Si will be described. Note that % in the components refers to mass %. The remaining components are Cu and unavoidable impurities.

[0025] Ni: 1.20~7.30% Ni is an essential element together with Si to precipitate intermetallic compounds and increase hardness, and also has the effect of improving formability. However, excessive addition significantly reduces electrical conductivity. There is no effect when added less than 1.20%, and electrical conductivity significantly decreases when added in excess of 7.30%. Therefore, Ni is set to 1.20-7.30%. Ni is preferably 2.25-6.00%, and more preferably 3.30-4.70%.

[0026] Silicon: 0.25 to 1.80% Si is an essential element for precipitating intermetallic compounds together with Ni to increase hardness, and also has the effect of improving formability. However, excessive addition significantly reduces electrical conductivity. If added less than 0.25%, there is no effect, and if added in excess of 1.80%, electrical conductivity significantly decreases. Therefore, the Si content is set to 0.25-1.80%. The Si content is preferably 0.55-1.45%, and more preferably 0.80-1.15%.

[0027] Mg: 0.40% or less Mg is an easily oxidized element, and is a component that causes residual pores, such as by reacting with oxygen to generate gas during molding, and is also an element that reduces electrical conductivity. If Mg is 0.40% or less, the effects are minor. On the other hand, if Mg is contained in an amount exceeding 0.40%, these adverse effects become significant. Therefore, Mg is set to 0 to 0.40%. Preferably, Mg is 0.10% or less, and more preferably, 0.02% or less.

[0028] Total of Zr, Cr, Nb, Mn, Fe, Zn, Sn: 0.00~2.00% When one or more of Zr, Cr, Nb, Mn, Fe, Zn, and Sn are contained, the total amount is 2% or less by mass. Although these elements have the effect of improving formability and hardness, compared with the case where Ni and Si, which are essential elements of the present invention, are added at a predetermined ratio, the balance between high hardness and high electrical conductivity is reduced by the inclusion of Zr, Cr, Nb, Mn, Fe, Zn, and Sn. This is because all of these elements are dissolved in the Cu matrix, thereby reducing the balance between high hardness and high electrical conductivity. From this perspective, when Zr, Cr, Nb, Mn, Fe, Zn, and Sn are contained, they can be treated as the total amount. And, when the total amount of these components is contained in excess of 2.00%, the adverse effects become significant. On the other hand, when the total amount of Zr, Cr, Nb, Mn, Fe, Zn, and Sn is 2.00% or less, the effect on the balance between high hardness and high electrical conductivity is minor. Therefore, the total content of Zr, Cr, Nb, Mn, Fe, Zn and Sn is set to 0.00 to 2.00%, more preferably the total content of Zr, Cr, Nb, Mn, Fe, Zn and Sn is set to 0.90% or less, and further preferably the total content of these components is set to 0.05% or less.

[0029] C, P, S: 0.000~0.020% each Since C, P, and S are all components that cause a decrease in electrical conductivity, it is desirable to strictly restrict the upper limit. If each component is contained at 0.020% or less, the effect is minor, but if it exceeds 0.020%, the adverse effect becomes significant. Therefore, the content of each of C, P, and S is set to 0.000 to 0.020%. Preferably, each of C, P, and S is 0.014% or less, and even more preferably, 0.009% or less.

[0030] Ni / Si: 3.00~6.00 The Ni / Si ratio is one of the most important indexes in the present invention. It is an index for achieving a balance between high hardness and high electrical conductivity while maintaining high formability. When the mass ratio of Ni to Si is less than 3.00 or more than 6.00, the balance between high hardness and high electrical conductivity of the layered product decreases. Therefore, the Ni / Si ratio is set to 3.00 to 6.00. Preferably, Ni / Si is 3.55 to 4.95, and more preferably 3.85 to 4.30.

[0031] Ni+Si: 1.50~9.00% As described above, Ni and Si are important essential elements in the present invention, and if the total content is less than 1.50%, high hardness cannot be obtained, and if it exceeds 9.00%, electrical conductivity decreases. Therefore, the total content of Ni+Si is set to 1.50-9.00%. Preferably, Ni+Si is 2.70-7.05%, and more preferably 3.90-5.10%.

[0032] Ag: 5.00% or less When Ag is added in the above Ni / Si ratio and Ni, Si ranges, the balance between high hardness and high electrical conductivity is further improved. Furthermore, the effect is higher when one or more of Zr and Cr are included. However, if added in excess, the effect is not observed. If added in excess of 5.00%, the effect of improving the balance between high hardness and high electrical conductivity is not observed, and the material price increases due to the expensive Ag. Therefore, when Ag is added as described in the second means, it is added in an amount of 5% or less. Preferably, Agg is 0.01 to 2.90%, more preferably 0.03 to 0.90%.

[0033] [About O and N] Since the powder in the present invention is an alloy, it inevitably contains gas components such as oxygen and nitrogen. In general, the content of these gas components differs between the surface and the interior of the powder, and the content of the gas components per powder weight depends on the total surface area (i.e., particle size). From the viewpoint of residual pores and non-metallic inclusions due to oxygen and nitrogen in the layered product, the amount of oxygen contained in the powder is preferably O: 1000 ppm or less, more preferably 500 ppm or less. The amount of nitrogen is preferably N: 300 ppm or less, more preferably 150 ppm or less.

[0034] [Average particle size of powder] The powder in the present invention can be suitably used in the additive manufacturing method. There are various additive manufacturing methods, but when powder is used as a raw material, a powder having an average particle size (volume average) of about 10 to 200 μm is used. Preferably, the average particle size is 15 to 40 μm in the case of the laser type powder bed method, 50 to 100 μm in the case of the electron beam type powder bed method, and 55 to 105 μm in the case of the deposition method. More preferably, the average particle size is 20 to 35 μm in the case of the laser type powder bed method, 65 to 85 μm in the case of the electron beam type powder bed method, and 70 to 90 μm in the case of the deposition method.

[0035] [Powder flowability, tap density, average circularity] The powder of the present invention can be suitably used in the layered manufacturing method. From the viewpoint of the uniformity of the powder bed by the squeegee (a plate for spreading the powder at a constant thickness) in the powder bed method and the stability in powder supply through a feeder in the deposition method, the flow rate of the powder is preferably 30s / 50g, more preferably 20s / 50g. From the same viewpoint, the tap density of the powder is preferably 50 to 80% of the true density, more preferably 60 to 78%. From the same viewpoint, the average circularity of the powder is preferably 0.70 or more, more preferably 0.75 or more.

[0036] Here, the flow rate can be measured by the Hall flow method, the tapped density by tapping the powder in a container and measuring the weight and volume, the true density by the gas displacement method, and the average circularity by Morphologi 4 (manufactured by Malvern Instruments), etc.

[0037] [Heat treatment temperature] In the layered product of the present invention, intermetallic compounds are precipitated by heat treatment, and the hardness and electrical conductivity are increased. The lower limit of the heat treatment temperature can be 400°C. The lower limit of the heat treatment temperature is preferably 600°C, more preferably 650°C, and even more preferably 700°C. The upper limit of the heat treatment temperature is preferably 900°C, and more preferably 850°C.

[0038] [Example] Cu alloy powders having the component compositions and Ni / Si ratios shown in Examples 1 to 29 and Comparative Examples 1 to 9 in Table 1 were prepared, and these Cu alloy powders were used to obtain shaped bodies by additive manufacturing. Since the powders shown in Table 1 were Cu alloy powders, the balance of the components shown in the table was Cu and unavoidable impurities. Of course, the examples in Table 1 are merely examples of the embodiments of the present invention, and it should be noted that the scope of the patent is not limited by these.

[0039] [Production of raw powder] The powders listed in Table 1 were obtained by gas atomization. The raw powder materials were placed in an alumina crucible in a vacuum or argon atmosphere, and the molten raw materials were melted by high-frequency heating. The molten alloy was then poured from a nozzle with a diameter of 5 mm at the bottom of the crucible, and immediately sprayed with high-pressure argon gas. The molten alloy was broken into fine droplets by this spraying, and cooled and solidified as it fell inside the tower of the atomization device, becoming alloy powder. The alloy powder was sieved through a mesh with 63 μm openings, and the powder that fell through the sieve was used as the raw powder for the subsequent additive manufacturing.

[0040] In addition, for all powders, the oxygen content O was 1000 ppm or less, the nitrogen content N was 300 ppm or less, the average particle size (volume average) was 15 to 40 μm, the flow rate was 30 s / 50 g or less, the ratio of tap density to true density was 50 to 80%, and the average circularity was 0.70 or more.

[0041] [Table 1]

[0042] [Additive manufacturing and heat treatment] Using these Cu alloy powders, we created a shaped body by additive manufacturing. Specifically, additive manufacturing was performed using a laser-heated powder bed type device (product name: EOS-M290) with an energy density of 200 J / mm 3 It was carried out in.

[0043] The base plate for molding was made of pure Cu, and molded objects measuring 12 x 12 x 12 mm (density, hardness) and 10 x 10 x 70 mm (conductivity) were produced. These molded objects were separated from the plate by wire cutting, and were subjected to heat treatment at the temperatures and times shown in Table 1, after which various evaluations were carried out. The results are shown in Table 2.

[0044] In the examples, the heat treatment was performed in an Ar atmosphere, and the specimens were held at a predetermined temperature for a predetermined time, followed by furnace cooling. The heat treatment temperature was also changed for some of the test specimens, and the effect of the heat treatment conditions on the balance between the hardness and electrical conductivity of the molded bodies of this alloy was also evaluated.

[0045] [Table 2]

[0046] [Evaluation of the relative density of the structure] The density of the molded body was measured using the Archimedes method. The weight of the test piece was measured in air and in water, the difference between the weights was used to derive the volume of the molded body, and the density was calculated by dividing the weight in air by this. The density of the raw material powder used was also measured using the gas displacement method. This method involves placing the powder in a container of a specified volume, introducing a fixed amount of gas into it, deriving the volume of the powder from the gas pressure, and dividing the weight of the powder by this to calculate the density. The density of the powder was taken as the true density of the alloy, and the relative density of the molded body was evaluated as "density of molded body / density of powder x 100 (%)".

[0047] [Evaluation of hardness of molded object] The hardness of the molded body was evaluated using a Vickers hardness tester. The test force was 2.94 N, and the average value of n=5 was evaluated.

[0048] [Evaluation of electrical conductivity of molded objects] To confirm the electrical conductivity of the molded object, the resistivity was measured by the four-terminal method (JIS C 2525). The reciprocal of the resistivity was taken as the electrical conductivity, and the value of pure Cu (5.9 × 10 7 The electrical conductivity (%IACS) of each sample was evaluated, with (S / m) being 100%IACS. The test pieces were machined to a size of 3 x 2 x 60 mm, and measurements were taken at room temperature, with a current of 4 A and a voltage drop distance of 40 mm.

[0049] The results of Table 2 are shown in a graph in Figure 1, with electrical conductivity (%IACS) on the vertical axis and Vickers hardness (Hv) on the horizontal axis. In the graph in Figure 1, the examples are plotted with ◯, and the comparative examples are plotted with ×. It can be seen that the group of examples has an excellent balance between hardness and electrical conductivity as a whole, compared to the group of comparative examples. Furthermore, Examples 21, 22, and 23, in which Ag was added, are shifted to the upper right of Figure 1, and have a better balance between hardness and electrical conductivity. Also, Comparative Examples 7, 8, and 9, which are binary Cu-Ni systems, have high electrical conductivity but extremely low hardness, and it can be seen from Figure 1 that the properties of both hardness and electrical conductivity are not compatible and are unbalanced.

[0050] As described above, the powders of Examples 1 to 29 shown in Table 1 all satisfy the prescribed components, Ni / Si ratio, and Ni+Si amount, and the molded bodies obtained by additive manufacturing using these powders by the powder bed method have a relative density of 99.0% or more, as shown in Table 2, and are confirmed to have excellent moldability. In addition, as shown in FIG. 1, the molded bodies using the powders of Examples 1 to 29 have a moderate balance between hardness and conductivity compared to the case of additive manufacturing using the conventional powder, and the plot positions of the Examples as a whole are shifted to the upper right direction in FIG. 1 from the plot positions of the Comparative Examples. That is, the Examples have both properties better than the Comparative Examples. In particular, Examples 21, 22, and 23 to which Ag is added are further shifted to the upper right direction in FIG. 1, and it was confirmed that they have both excellent hardness and conductivity.

[0051] In Comparative Example 1, the Ni and Si contents were too small, and the Ni+Si content was also too small, resulting in poor relative density and poor moldability. In Comparative Example 2, Ni and Si were excessive, and Ni+Si was also excessive, resulting in a significant decrease in electrical conductivity. In Comparative Examples 3 and 6, the Ni / Si ratio was higher than average, and in Comparative Examples 4 and 5, the Ni / Si ratio was lower than average, and all of the results showed a poor balance between hardness and electrical conductivity compared to the Examples. Comparative Examples 7, 8, and 9 are binary Cu-Ni systems containing only trace amounts of Si as an impurity, so the Ni / Si ratio is significantly off and the hardness is extremely low, resulting in a poor balance between hardness and electrical conductivity, which cannot be achieved simultaneously.

Claims

1. In mass percent, Ni: 1.20-7.30%, Si: 0.25-1.80%, Mg: 0.40% or less, The total of one or more of Zr, Cr, Nb, Mn, Fe, Zn, and Sn: 0.00 to 2.00%, C: 0.000-0.020%, P: 0.000-0.020%, S: 0.000 to 0.020%; The balance is Cu and unavoidable impurities. And in the above components, Ni / Si: 3.00 to 6.00 Ni + Si: 1.50 to 9.00%; Cu alloy powder for additive manufacturing.

2. In addition to the components according to claim 1, Further, the Cu alloy powder for additive manufacturing contains, by mass%, Ag: 5.00% or less, the balance being Cu and unavoidable impurities, and the Ni / Si: 3.00 to 6.00 and Ni + Si: 1.50 to 9.00%.

3. A molded body produced by additive manufacturing using the Cu alloy powder for additive manufacturing according to claim 1 or 2.